2014
DOI: 10.4301/s1807-17752014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the Marketing Information System in the Clothing Retail Business

Abstract: This paper has the purpose of being familiarized with the benefits of the marketing information system in companies that operate in the retail business. A field research was done in a major clothing retailer, by means of a case study that consisted of interviews with two employees of the company, one from the top management and one from the marketing area, based on a semi-structured script , in addition to a documental analysis. The results indicate that information and its systematization possess great import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…(p-value) of .000 is less than α (0.05), hence, a significant correlation is found between marketing intelligence and business competitive advantage. This result is supported in the findings of Queiroz, & Oliveira (2014) which indicated that marketing intelligence and the systematization of information in the market settings "possess great importance for the development of competitiveness, contributing to development of the operations and to promotion of new business opportunities".…”
Section: Discussion Of Findingsmentioning
confidence: 55%
“…(p-value) of .000 is less than α (0.05), hence, a significant correlation is found between marketing intelligence and business competitive advantage. This result is supported in the findings of Queiroz, & Oliveira (2014) which indicated that marketing intelligence and the systematization of information in the market settings "possess great importance for the development of competitiveness, contributing to development of the operations and to promotion of new business opportunities".…”
Section: Discussion Of Findingsmentioning
confidence: 55%
“…These changes and pressures force business firms to respond in an innovative manner sustaining competitive advantage in the marketplace [13]. Market intelligence refer to business ability to information processing, interpreting and disseminating to enhance the coordination process among business partners being agile to respond to changing environment in order to enter new markets that have to maximize market intelligence capabilities which require details knowledge of competitors, best practices through capturing and processing relevant information about specific market environment [14]. Therefore, marketing intelligence is information about the business environment that support decision makers in the process of developing their marketing strategies according to surrounding environment.…”
Section: Marketing Intelligencementioning
confidence: 99%
“…An efficient ITbased marketing information system allows an organization to systematize and, to a greater or lesser extent, automate many of the routine tasks that are part of many jobs (Brady et al, 2002). The search for the creation of a competitive advantage can be maximized if a company uses the marketing information system effectively (De Queiroz and Oliveira, 2014).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Kotler and Keller (2006) specified marketing IS into the following subsystems: internal records; marketing intelligence; marketing research; and analysis and support to market decisions. By analyzing the benefits provided by the marketing information system, it is possible to see the dedication of a company to obtain information about its customers to strengthen their relationship, as well as the search for meeting their customers' needs (De Queiroz and Oliveira, 2014). A marketing IS provides methods for interpreting the information it delivers and is very important for planning and analysis (Hakhua et al, 2013).…”
Section: Introductionmentioning
confidence: 99%